The adventures of Lewis and Clark - De Kay, Ormonde, 1923-; Severin, John Powers (New York, Random House, 1968)
An easy-to-read history of the expedition which explored the unknown Louisiana Purchase territory and Pacific Northwest from St. Louis to the mouth of the Columbia River.